cot(x) = cos(x)/sin(x)
------------------------------
Now you have:
[cos(x)/sin(x)] - cos(x) + cos(x)
------------------------------
What's the answer?
cotxsinx - cosx + cosx
Does this equal cos x ?
cos/sin * sin = cosx
3 answers
By the way, the person who just commented is me. I should've changed my name.
cotxsinx - cosx + cosx
Putting in cotx = (cos/sinx),
(cosx/sinx)*sinx + (- cosx + cosx)
= cosx*(sinx/sinx) + 0
= cosx*1
= cosx
Putting in cotx = (cos/sinx),
(cosx/sinx)*sinx + (- cosx + cosx)
= cosx*(sinx/sinx) + 0
= cosx*1
= cosx